Can family involvement improve educational outcomes in developing countries? - Anke Weber (Verein für Socialpolitik, 2010)
Low-income countries struggle to provide their populations with universal primary education, albeit lack of the required financial resources. Strategies are sought after to more efficiently use existing educational equipment in these countries. In particular, the role of families and their involvement in schooling to improve educational outcomes has gained increased scholarly attention. While evidence from the developed world proposes strong beneficial effects of family involvement, applications to low-income countries are surprisingly scarce. This paper provides a first test of the impact of three family involvement components, namely monitoring school attendance, improving family-school relationship, and providing school-lunch, on educational outcomes in the representative low-income country Tanzania. Results from the unique school mapping dataset on over 600 communities in Tanzania confirm the relevance of family involvement to increase enrolment and the quality of education. These effects are particularly relevant for poor and less educated parents.
Keywords: I20; O10; H41; 330; Parental involvement; primary education; socioeconomic status; ethnicity; developing countries